Linear and quadratic solid-shell elements for quasi-static and dynamic simulations of thin 3D structures - Wang, Peng (Strojniški vestnik, 2017)
A family of prismatic and hexahedral solid%shell (SHB) elements, with their linear and quadratic versions, is proposed in this work to model thin structures. The formulation of these SHB elements is extended to explicit dynamic analysis and large-strain anisotropic plasticity on the basis of a fully three-dimensional approach using an arbitrary number of integration points along the thickness direction. Several special treatments are applied to the SHB elements in order to avoid all locking phenomena and to guarantee the accuracy and efficiency of the simulations. These solid-shell elements have been implemented into ABAQUS standard/quasi-static and explicit/dynamic software packages. A number of static and dynamic benchmark problems, as well as a simulation of the deep drawing of a cylindrical cup, have been conducted to assess the performance of these SHB elements.
Keywords: dinamične obremenitve; globoki vlek; končni elementi; kvadratični telesno-lupinski elementi; kvazistatične obremenitve; linearni telesno-lupinski elementi; metoda domnevnih deformacij; tankostenske 3D-konstrukcije